New horizons in surgical treatment of ground-glass nodules of the lung: experience and controversies - Chen D; Dai C; Kadeer X; Mao R; Chen YB; Chen C (Dove Medical Press, 2018)
Donglai Chen,1 Chenyang Dai,1 Xiermaimaiti Kadeer,1 Rui Mao,1 Yongbing Chen,2 Chang Chen1 1Department of Thoracic Surgery, Shanghai Pulmonary Hospital, Tongji University School of Medicine, Shanghai, 2Department of Cardiothoracic Surgery, the Second Affiliated Hospital of Soochow University, Suzhou, Jiangsu, China Abstract: Ground-glass nodule (GGN) is defined as a nodular shadow with ground-glass opacity that is generally associated with the early-stage lung adenocarcinoma. Nowadays, GGNs of the lung are increasingly detected with thin-section computed tomography scan. GGNs are categorized as pure GGNs and mixed GGNs according to the images from a high-resolution computed tomography. Meanwhile, it is routine to divide GGNs into different categories according to the number, solitary, or multiple, the management of which there is very different. A great number of studies have been conducted to analyze the different characteristics of GGNs in various aspects ranging from radiology, pathology, and surgery to molecular biology. However, plenty of problems still remain unsolved, ranging from the preoperative localization to intraoperative surgical resection procedure, the lymphadenectomy, and sampling of lymph nodes, as well as the accuracy of frozen sections. There has been a large volume of updated published information summarizing recently emerging and rapidly progressing aspects of surgical treatment of solitary and multiple GGNs with the unsolved problems mentioned above. However, there have been few specific reviews of surgical treatment of GGNs so far. This review presents a timely outline of advances in relevant experience and controversies of GGNs for a better understanding of this kind of lesion. Keywords: ground-glass nodules, early stage lung adenocarcinoma, therapeutic strategy, preoperative localization, surgical pathology, lymph node management